Why Do (Some) Households Trade So Much? - Linnainmaa, Juhani T. (Review of Financial Studies, 2011)
When agents can learn about their abilities as active investors, they rationally “trade to learn ” even if they expect to lose from active investing. The model used to develop this insight draws conclusions that are consistent with empirical study of household trading behavior: Households ’ portfolios underperform passive investments; their trading inten-sity depends on past performance; and they begin by trading small sums of money. Using household data from Finland, the article estimates a structural model of learning and trad-ing. The estimated model shows that investors trade to learn even if they are pessimistic about their abilities as traders. It also demonstrates that realized returns are significantly downward-biased measures of investors ’ true abilities. (JEL D10, G11) While most households adjust their stock portfolios only infrequently, some trade very actively and underperform passive investments.1 I ask whether a model in which investors rationally learn from experience can explain this be-havior, and, if so, what the model tells us about households ’ beliefs. In my model, investors are uncertain about their abilities and learn as they trade. If the value of observing another signal is high, then an investor trades even if she expects to lose money, thus apparently trading “too much. ” If a trade is successful, the investor infers skill and subsequently trades more. If an investor loses money, she will infer less skill and subsequently trade less. After enough losses, she stops trading altogether. Investors who are especially uncertain about their abilities trade small amounts early in their careers until